2013
DOI: 10.1136/gutjnl-2013-305607
|View full text |Cite
|
Sign up to set email alerts
|

Changes in medical treatment and surgery rates in inflammatory bowel disease: a nationwide cohort study 1979–2011

Abstract: Introduction Treatment possibilities have changed in inflammatory bowel disease (IBD). We assessed changes in medical treatment and surgery over time and impact of medications on risk of surgery in a population-based cohort. Methods 48 967 individuals were diagnosed with IBD (Crohn's disease (CD), 13 185; ulcerative colitis (UC), 35 782) during 1979–2011. Cumulative probability of receiving 5-aminosalicylic acids (5-ASA), topical, oral corticosteroids, thiopurines, and tumour necrosis factor-α (TNF-α) blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
208
8
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(255 citation statements)
references
References 23 publications
(31 reference statements)
23
208
8
8
Order By: Relevance
“…To reduce the risk of bias, due to the introduction of these novel techniques in different years, upper gastrointestinal disease (L4) was regarded were 2.0% and 8.4% at 1 and 5 years, respectively, from diagnosis and are lower than in some earlier reports from referral centres. However, the time period represents the early years within the era of biologics, when the treatment strategies were yet to be established and biologics often introduced late during the disease course as a third-line treatment, and other population-based studies from these years have revealed similar figures (2,5,7,8). Therefore, the study was not designed to address the question of disease modification due to anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the risk of bias, due to the introduction of these novel techniques in different years, upper gastrointestinal disease (L4) was regarded were 2.0% and 8.4% at 1 and 5 years, respectively, from diagnosis and are lower than in some earlier reports from referral centres. However, the time period represents the early years within the era of biologics, when the treatment strategies were yet to be established and biologics often introduced late during the disease course as a third-line treatment, and other population-based studies from these years have revealed similar figures (2,5,7,8). Therefore, the study was not designed to address the question of disease modification due to anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Medical therapy advanced with the use of immunomodulators and the introduction of biologics. Changes in medical therapy and surgical practice over time might have influenced the natural history of the disease and possibly reduced surgery rates (1)(2)(3)(4)(5)(6)(7). However, epidemiological studies that have evaluated the effect of immunomodulators on surgery rates have yielded conflicting results (7)(8)(9).…”
Section: Introduction and Aimsmentioning
confidence: 97%
“…Although similar, our results cannot be strictly compared with those from the IBSEN study because this is not a population-based study but a monocentre retrospective cohort. The population-based cohort of Rungoe et al [21] demonstrated a decreased probability rate of surgery at 5 years in CD and UC in the last 10 years but without a surgery-sparing effect of newer medications. Due to the retrospective character of the study, the type of resection was not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of surgery for IBD have been reported to be decreasing. 5,6 Studies have also shown that women with active disease or previous abdominal surgery had reduced pregnancy rates. [7][8][9] A population-based study from Sweden showed that women with IBD had twice the rate of caesarean section compared with control women, and that women with UC had increased rates of venous thromboembolism (VTE).…”
Section: Introductionmentioning
confidence: 99%